2018
DOI: 10.1016/j.ymben.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the transcription factors GntR1 and RamA enhance the growth and central metabolism of Corynebacterium glutamicum

Abstract: Evolution, i.e. the change in heritable characteristics of biological populations over successive generations, has created the diversity of life that exists today. In this study we have harnessed evolution to create faster growing mutants of Corynebacterium glutamicum, i.e. to debottleneck growth rate of this highly important industrial workhorse. After approximately 1500 generations of Adaptive Laboratory Evolution (ALE) in defined minimal medium with glucose, we obtained faster growing mutants with specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 68 publications
4
31
1
Order By: Relevance
“…Coupling production to reactions or pathways important for growth bears the potential to select improved strains by laboratory evolution. This strategy has been successful for selecting faster growing C. glutamicum strains ( Pfeifer et al, 2017 ; Radek et al, 2017 ; Wang Z. et al, 2018 ) or strains more tolerant to methanol ( Leßmeier and Wendisch, 2015 ), lignocellulose derived inhibitors ( Wang X. et al, 2018 ) or thermal stress ( Oide et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coupling production to reactions or pathways important for growth bears the potential to select improved strains by laboratory evolution. This strategy has been successful for selecting faster growing C. glutamicum strains ( Pfeifer et al, 2017 ; Radek et al, 2017 ; Wang Z. et al, 2018 ) or strains more tolerant to methanol ( Leßmeier and Wendisch, 2015 ), lignocellulose derived inhibitors ( Wang X. et al, 2018 ) or thermal stress ( Oide et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The time needed for biomass production represents a key factor in the economic success of biotechnological processes. While ALE approaches have been intensively explored to accelerate the growth of E. coli , so far, only two recent studies have reported on the evolution of C. glutamicum towards higher growth rates on glucose minimal medium (Table ) . Interestingly, these studies revealed similar key targets for enhancing metabolic flux and increasing substrate uptake rates for both species, indicating that microorganisms follow similar principles to adapt to fast growth.…”
Section: Accelerating Growth On Glucosementioning
confidence: 99%
“…In another recent ALE experiment, C. glutamicum cultures were evolved for about 1500 generations in defined media with glucose . The evolved cell line was found to lack large parts of the CGP3 element.…”
Section: Accelerating Growth On Glucosementioning
confidence: 99%
See 2 more Smart Citations